Uso de colostro materno em recém-nascidos prematuros com suspeita de sepse neonatal precoce - Paula, Camila Beatriz de (2022)
The oropharyngeal administration of colostrum (OOC) in preterm infants may offer immunological benefits through the contact of protective biofactors in breast milk with oropharyngeal-associated lymphoid tissue (OFALT). Researchers have studied such effects on necrotizing enterocolitis (NCE), late neonatal sepsis and also on intestinal maturation and interference in the formation of microbiota through human milk oligosaccharides (HMOS) present in colostrum. The main objective of the study is to elucidate the influence of early administration of maternal colostrum in the oropharynx of premature babies with clinical suspicion of early neonatal sepsis, and to monitor clinical outcomes until hospital discharge. The methodology consisted of selecting 20 newborns, with clinical criteria for the diagnosis of early neonatal sepsis, admitted to the Neonatal Intensive Care Unit (NICU) of a public hospital, from February to November 2021. In the treatment group, within 48 hours of life, 0.2 ml of raw colostrum was placed on the right and left oropharyngeal mucosa, totaling eight daily administrations, until the 5th day of life. The control group received no intervention with oral colostrum. Patients were followed up until hospital discharge. Blood samples were collected at three times: at admission for HMC and real-time PCR [trPCR]); between 12 to 24 hours of life for HMG, PCR, PCT and IL-6 and with 72 hours of life for HMG and PCR. In the end, patients remained in the research if they had suspected neonatal sepsis, or confirmed by HMC and/or presence of genomic DNA by trPCR, compatible clinical manifestations and had received 75% or more of the recommended doses of oral colostrum. The results showed a significant association in the group of newborns who received colostrum in relation to the group without colostrum, regarding weight recovery from birth to 15 days of life. There was no statistical difference for the other variables related to clinical outcomes of early neonatal sepsis. The study concluded that newborns who received oral colostrum in the first days of life reached birth weight faster than babies who did not. Therefore, further studies with a larger population are necessary to prove other correlated benefits. Descriptors: colostrum; preterm newborns; early-onset neonatal sepsis; molecular biology;